Analysis of the Influence of Islamic Investment in the Capital Market on Economic Growth in Indonesia - Erna Setiyowati (Yayasan Rahmat Islamiyah, 2026)
This study analyzes the influence of Islamic investment in the capital market on Indonesia’s economic growth, focusing on three main instruments, namely Islamic stocks, Islamic mutual funds, and corporate sukuk, while employing inflation as a control variable. Using a quantitative approach with quarterly time series data from 2011 to 2024, this research applies the Vector Error Correction Model (VECM) to capture both long-run relationships and short-run dynamics among the variables. The results show that Islamic mutual funds have a positive and significant effect on Gross Domestic Product (GDP) in the long term, with the highest contribution reaching 28 percent, whereas Islamic stocks exhibit a significant negative effect. Corporate sukuk are found to have no significant impact on GDP, possibly due to their relatively small market share. Inflation as a control variable shows no significant effect during the study period. These findings indicate that not all Islamic investment instruments positively affect economic growth, underscoring the need for massive improvement in Islamic financial literacy to shift investors from short-term speculative patterns toward long-term productive investment in the real sector. This study is limited to three capital market instruments and the 2011–2024 period; thus, future research is encouraged to expand the scope of instruments, extend the observation period, and employ alternative proxies to gain a more comprehensive understanding.